Analysis of Dribbling Skills in Football Sports in SSB Gasak FC Club - Cahyo, Septian Tri; Widodo, Haryo Mukti; Himawan, Agus; Hidayatullah, Fajar (Universitas Negeri Surabaya, 2024)
Purpose: This research aims to determine the level of dribbling ability of Gasak FC Bangkalan players. Materials and Methods: Dribbling skills are one of the basic skills that are very important in the game of football, which involve the player's ability to control the ball while moving on the field. The research method used is descriptive quantitative with a survey approach. Data was collected through direct observation and measurement of dribbling skills using validated standard tests. Participants in this research were 15 football players from SSB GASAK FC. Result: The research results show that the dribbling skills of Gasak FC players are included in the Fair category with an average of 20.42 seconds. Factors such as training frequency, training quality, and intrinsic motivation also have a significant influence on a player's dribbling skills. Conclusion: These findings provide insight for coaches and club managers about the importance of developing training programs that focus on improving dribbling skills, as well as the importance of paying special attention to young players to develop strong basic skills from an early age